A Crystalline Carbon Nitride Based Near‐Infrared Active Photocatalyst. (16th September 2022) - Zhai, Boyin; Li, Hongguan; Gao, Guangying; Wang, Ying; Niu, Ping; Wang, Shulan; Li, Li
Abstract: Efficient utilization of near‐infrared (NIR) light that takes a primary percentage of the solar spectrum is of great significance for practical applications of photocatalysis. However, development of singular NIR‐based photocatalysts still remains a grand challenge. Herein, a NIR‐based crystalline carbon nitride photocatalyst is proposed by using a molten‐salt assisted protocol with carbohydrazide as the oxygen‐containing precursor. Different from the doping strategy that always leads to structural damage and crystallinity decrease, structural oxygen arising from the special precursor itself is introduced into the framework of C3 N4 with highly crystalline structure formed. The n→π* excitation is therefore activated with the absorption edge extended remarkably to 1400 nm. Theoretical calculations also reveal that the local internal electric field is simultaneously generated for promoting the charge separation/migration kinetics. Benefiting from structural oxygen incorporation and crystalline structure formation, the synthesized material shows a significantly enhanced visible‐light (λ > 420 nm) hydrogen production reactivity compared with the benchmark carbon nitride, and more importantly an active NIR hydrogen generation (λ > 700 nm) and long‐wavelength overall water splitting (λ = 600 nm) capability that is rarely reported for singular photocatalysts. This study showcases an illustration of promising singular NIR photocatalysts for efficient solar fuel production. Abstract : Benefiting from structural oxygen incorporation and crystalline structure formation through the molten salt assisted treatment of oxygen‐containing precursor carbohydrazide, a singular crystalline C3 N4 shows the extended absorption edge to 1400 nm and high NIR photocatalytic activity.